Development of a Unified Methodology for Risk-oriented Sanitary and Hygienic Monitoring of Advisory and Diagnostic Health Care Centers - Kamilova, R.T.; Ataniyazova, R.A.; Isakova, L.I.; Absattarova, V.K. (Asian Pacific Journal of Environment and Cancer, 2021)
Nowadays, there are crucial issues for sanitary and hygienic monitoring of activity risk assessment of the health care facilities for identify internal and external factors occupational conditions of health risk development for medical workers and patients in health care facilities. The objective of the study was to develop a methodology for risk-oriented monitoring of health care facilities, taking into account the classes of working conditions of medical staff. The development of the unified methodology of the risk-oriented monitoring of the health care facilities’ activities taking into account the classes of working conditions of the medical staff and sanitary and technical provision made it possible to establish that the greatest probability of the risk and health hazard development for the medical staff in the advisory and diagnostic health care centers was represented by intellectual, sensory and emotional loads (working conditions classes - 3.2, 3.3) as well as by the biological factor (3.4) with thefinal identification equal to 16 scores, which corresponds to a high risk level (red); the identification of the probability of risk and impairment to health by the hardness of the work process (3.2) is set at 9 scores - medium risk (yellow), and by the parameters of the microclimate, regardless of the period of the year (3.1), corresponds to 6 scores - low risk (green).